The Effect of Organizational Citizens' Behavior (OCB), Competence, and Organizational Culture on Performance: Employee Satisfaction as Mediating Variable - St.Hatidja St.Hatidja; Herminawaty Abubakar; Hernita Hernita; I Gede Arya Pering Arimbawa; Aditya Halim Perdana Kusuma Putra (Universitas Dharma Wacana, 2022)
The purpose of this study was to analyze the influence organizational citizenship behavior, competence, and organizational culture on employee job satisfaction, analyze the influence of organizational citizenship behavior, competence and organizational culture on employee performance, analyze job satisfaction on employee performance and analyze the influence of organizational citizenship behavior, competence, and organizational culture on performance through employee job satisfaction. The research was carried out in Makassar City, precisely at PT. Bank Mandiri with a population of 782 employees and a sample of 265 people as respondents based on the Slovin formula. Questionnaire results data were analyzed using the Structural Equation Model using AMOS 20. The results of the study found that organizational citizenship behavior had a negative and not significant effect on employee job satisfaction. The cause of the OCB variable has a negative effect because all organizational citizenship behavior indicators are not easy or difficult to apply by employees which cause employees to not behave comparatively and innovatively in dealing with and carrying out their work, while the causes of organizational citizenship behavior have no significant effect on job satisfaction, because employees do not have the orientation and satisfactory job prospects in developing good work behavior. The behavior of organizational members has a negative and insignificant effect on employee performance because all indicators do not support employees being able to develop their behavior to achieve optimal work results. The behavior of organizational members has a negative and insignificant effect on performance through employee job satisfaction. This is because variable indicators are difficult for employees to apply. After all, the demands for services carried out by employees must be by the systems, procedures, policies, and provisions that apply within an organization, making it difficult to develop behavior that is following the wishes and interests of customers. And this is what causes employee performance to be difficult to increase and through job satisfaction employees feel dissatisfied with what they are doing